The level of tumour necrosis factor-alpha and its relationship to the cognitive function of Malayan-Mongoloid patients with schizophrenia - Mustafa M. Amin; Abdul Rasyid; Elmeida Effendy; Nurmiati Amir; Nurmiati Amir; Dwi Anita Suryandari (Medicinski glasnik, 2020)
Aim: Schizophrenia is a mental disorder and one of the suspected causes is cytokines. One of them is tumour necrosis factor-alpha (TNF-?). Cytokines have the potential to affect cognitive function. The study aimed to find a correlation of TNF-? level with the Mini-Mental State Examination (MMSE) score in patients with schizophrenia (PwS), and comparing the level of TNF-? levels between PwS and healthy controls. Methods: We conducted a cross-sectional analytic study and the study designs were correlation and comparative analysis, i.e. using a Mann-Whitney U test. A total number of 100 subjects were collected, and they were divided into two groups of PwS and control group, respectively. Results: The results found that most of the PwS subjects were 39 men (78.0%), while the control group were 28 men (56.%). The differences in TNF-? levels between PwS and control groups were found to be significant p <0.001, there was no significant correlation between TNF-? level and the score of MMSE of the PwS with p = 0.938, with a very weak correlation that was r = -0.011, and a negative correlation direction. Conclusion: There was a significant difference between TNF-? level of PwS and control group, i.e. PwS group had lower TNF-? level compared to the control group. The TNF-? level of PwS group had a very weak effect on the cause of cognitive dysfunction in PwS group, yet the higher level of it could reduce MMSE score in PwS group.
Keywords: cytokines; cognitive dysfunction; psychotic disorders